2017
DOI: 10.15252/embj.201797527
|View full text |Cite
|
Sign up to set email alerts
|

A forceful connection: mechanoregulation of oncogenic YAP

Abstract: The Yes‐associated protein (YAP) is an important transcriptional co‐activator that mediates the cellular response to mechanical and cytoskeletal cues. In two recent papers published in The EMBO Journal, Dae‐Sik Lim and colleagues show how YAP activity affects cancer formation and metastasis via a crosstalk with myocardin‐related transcription factors (MRTFs; Kim et al, 2017) and SKP2‐dependent cell cycle progression (Jang et al, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…RAS-ERK signalling also crosstalks with the YAP/TAZ pathway. YAP/TAZ transcriptional regulators play critical roles in mechanotransduction [ 45 ], and their role in cancer development and progression has been widely studied and previously reviewed [ 46 , 47 ]. YAP/TAZ are transcriptional coactivators of the Hippo pathway that shuttle between the cell cytoplasm and nucleus in response to mechanical cues, such as the activation of Rho and cortical tension [ 45 ].…”
Section: Oncogenic Mechanosensing and Mechanotransductionmentioning
confidence: 99%
“…RAS-ERK signalling also crosstalks with the YAP/TAZ pathway. YAP/TAZ transcriptional regulators play critical roles in mechanotransduction [ 45 ], and their role in cancer development and progression has been widely studied and previously reviewed [ 46 , 47 ]. YAP/TAZ are transcriptional coactivators of the Hippo pathway that shuttle between the cell cytoplasm and nucleus in response to mechanical cues, such as the activation of Rho and cortical tension [ 45 ].…”
Section: Oncogenic Mechanosensing and Mechanotransductionmentioning
confidence: 99%
“…A recent study demonstrated that YAP associates with YY1 and EZH2 on the genome to inhibit p27 expression at the transcriptional level [ 208 ]. Additionally, in response to mechanical cues, YAP elevates the transcription of ubiquitin ligase Skp2, which subsequently forms a complex with Skp1-Cullin-1-F-box (SCF) to target p21 and p27 for proteasomal degradation [ 209 , 210 ]. By collaborating with FOXM1, an essential cell cycle transcription factor that promotes G1/S progression in part by increasing the Skp2-mediated degradation of p21 and p27, YAP further prompts E2F-mediated gene expression [ 151 , 211 ].…”
Section: The Core Of Mammalian Hippo Pathway In Other Phases Of the Cell Cyclementioning
confidence: 99%